The Balassa-Samuelson effect in 'East & West': Differences and similarities - Martin Wagner (Institute for Advanced Studies (IHS), 2005)
Based on two detailed Balassa-Samuelson (BS) studies, Wagner and Hlouskova (2004) for eight Central Eastern European countries (CEECs) and Wagner and Doytchinov (2004) for ten Western European countries (WECs), this study assesses the differences and similarities of the BS effect between these two country groups. The econometric results show that the BS effect may have been overestimated in previous studies due to application of inappropriate first generation panel cointegration methods. When appropriately quantified, the BS effect itself explains RER movements respectively inflation differentials only to a small extent. However, extended BS relationships that include additional variables allow for an adequate modelling of inflation. Based on the comparative analysis we draw some conclusions for monetary policy in the future enlarged Euro Area.
Keywords: F02; O40; O57; P21; P27; 330; Balassa-Samuelson effect; Central and Eastern Europe; Western Europe; non-stationary panels; inflation simulations; Panel; Kointegration; Osteuropa; Westeuropa; Balassa-Samuelson Effekt